2007
DOI: 10.1111/j.1469-8749.2006.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

A neurophysiological perspective on sleep and its maturation

Abstract: Neurophysiological studies of sleep have increasingly focused on underlying dynamic processes. This would appear particularly relevant to the developmental aspects of sleep. Involvement of sleep‐dependent mechanisms in emotional processing, as well as perceptual‐sensory, perceptual‐motor, and cognitive learning, mostly studied in adults, may play major roles in development. Rapid eye movement (REM) sleep, which is generated by complex neuronal interactions within the pontine reticular formation, and non‐REM sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Thus, the median 'bursting index' (see Wagenaar et al, 2005) calculated over the most active 5 min segment of 15 min recordings proved to be only 0.63 in preparations with added brainstem (range: 0.24-0.84, n = 5) as compared with 0.80 (0.59-1.00) for an equal number of control explants (U = 3.5, p < 0.05). With such an approach, mechanisms underlying slow-wave sleep-dependent consolidation of learned material (e.g., Dan and Boyd, 2006;Hoffman and McNaughton, 2002;Steriade and Timofeev, 2003) or re-adjustment of overall cortical excitability and/or circuitry (Frank et al, 2001(Frank et al, , 2006Tononi and Cirelli, 2006) could be approached using a stimulus-related plasticity protocol (Eytan et al, 2004;Marom and Shahaf, 2002;Shahaf and Marom, 2002) during a physiologically 'aroused' state, followed by a period of sleep-like 'brain wave' activity (see Wagenaar et al, 2005Wagenaar et al, , 2006a. A reversible induction of tonic (i.e., sustained, non-bursting) firing has been reported in cultures subjected to circulating cholinergic agonists (Tateno et al, 2005a,b) but, since this is more a 'model' for paradoxical sleep than for wakefulness, it is likely to be less than ideal for carrying out realistic learning or memory experiments: the inclusion of monoaminergic in addition to cholinergic transmitters or agonists would be required, namely, for approximating the physiological state of the waking brain (see Adrien and Lanfumey, 1986;Corner, 1990;Hasselmo, 1995;Jouvet, 1972Jouvet, , 1999.…”
Section: Selection Of Suitable Preparations ('Model Systems')mentioning
confidence: 99%
“…Thus, the median 'bursting index' (see Wagenaar et al, 2005) calculated over the most active 5 min segment of 15 min recordings proved to be only 0.63 in preparations with added brainstem (range: 0.24-0.84, n = 5) as compared with 0.80 (0.59-1.00) for an equal number of control explants (U = 3.5, p < 0.05). With such an approach, mechanisms underlying slow-wave sleep-dependent consolidation of learned material (e.g., Dan and Boyd, 2006;Hoffman and McNaughton, 2002;Steriade and Timofeev, 2003) or re-adjustment of overall cortical excitability and/or circuitry (Frank et al, 2001(Frank et al, , 2006Tononi and Cirelli, 2006) could be approached using a stimulus-related plasticity protocol (Eytan et al, 2004;Marom and Shahaf, 2002;Shahaf and Marom, 2002) during a physiologically 'aroused' state, followed by a period of sleep-like 'brain wave' activity (see Wagenaar et al, 2005Wagenaar et al, , 2006a. A reversible induction of tonic (i.e., sustained, non-bursting) firing has been reported in cultures subjected to circulating cholinergic agonists (Tateno et al, 2005a,b) but, since this is more a 'model' for paradoxical sleep than for wakefulness, it is likely to be less than ideal for carrying out realistic learning or memory experiments: the inclusion of monoaminergic in addition to cholinergic transmitters or agonists would be required, namely, for approximating the physiological state of the waking brain (see Adrien and Lanfumey, 1986;Corner, 1990;Hasselmo, 1995;Jouvet, 1972Jouvet, , 1999.…”
Section: Selection Of Suitable Preparations ('Model Systems')mentioning
confidence: 99%
“…Furthermore, considering younger populations, although increased odds for the presence of SB were observed in regard to barbiturate and methylphenidate, an extrapolation of results to adults is not recommended, as further evidence about this topic is still lacking. Moreover, it is suggested that sleep pattern and neurophysiological characteristics might vary from childhood to adulthood, possibly generating different medication responses.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important observation because, without considering the modulatory influence of the thalamus on the SCN, these delays cannot be explained. Research has shown that the RE neurons can only become hyperpolarized and produce spindles when the various excitatory inputs to the thalamus diminish to a certain level [40]. The promotion of sleep hygiene in children with attention deficit hyperactivity disorder is based on the intent to reduce excitatory stimuli prior to habitual bedtime, as it is well known that it may shorten sleep onset.…”
Section: Dlmo and Nrem Sleep Gatementioning
confidence: 99%